Leadership and Work Discipline in Foreign Language Teaching: Explaining German Language Teacher Performance in Indonesian Island Schools - Henderika Serpara, Rudolf Kempa, Izaak Hendrik Wenno, Theresia Laurens (Journal of Daoist Studies, 2026)
Teacher performance is a critical factor in the effectiveness of foreign language teaching, particularly in geographically isolated school contexts where professional support and instructional resources are limited. However, empirical evidence remains scarce regarding how school leadership and teacher work discipline jointly influence foreign language teacher performance in such settings. This study aims to examine the individual and combined effects of principal leadership and work discipline on the performance of German language teachers in Indonesian island schools. A quantitative correlational design was employed, involving 44 German language teachers from six senior high schools in the Ambon and Lease Islands. Data were collected through structured questionnaires and analyzed using multiple linear regression. The results revealed a strong and statistically significant relationship between leadership, work discipline, and teacher performance (R = 0.789, p < 0.001), with work discipline emerging as the strongest predictor. Together, the variables explained 62.3% of the variance in teacher performance. These findings demonstrate that consistent professional behavior and supportive leadership structures are key drivers of effective foreign language teaching in remote contexts. The study contributes empirical evidence from an under-researched educational setting and highlights the need for integrated strategies that strengthen both leadership practices and teacher discipline to improve instructional quality.